2000
DOI: 10.1034/j.1600-079x.2000.290302.x
|View full text |Cite
|
Sign up to set email alerts
|

Low urinary 6‐sulphatoxymelatonin levels in patients with coronary artery disease

Abstract: A decrease in nocturnal serum melatonin levels was reported in patients with clinically uncharacterized coronary artery disease. To assess whether there was a correlation between melatonin production and disease stage, we measured the nocturnal urinary excretion of 6-sulphatoxymelatonin (an index of blood melatonin concentration) in patients with chronic stable or unstable coronary disease and in a group of age-matched controls. Three groups of individuals were studied: a) 24 healthy subjects (mean age: 63 +/-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
53
0
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(59 citation statements)
references
References 25 publications
(32 reference statements)
1
53
0
4
Order By: Relevance
“…In a study with long-term follow-up, Kurunlahti et al [6] pointed out that there was an association between disc diseases and fatal ischemic heart disease. Furthermore, it has been suggested that patients with ischemic coronary disease have a low MEL production rate, with greater decreases in those with higher risk of cardiac infarction and/or death [22]. Now, it is generally accepted that the existence of advanced aortic atherosclerosis, presenting as calcific deposits in the posterior wall of the aorta, increases a person's risk for development of disc degeneration and is associated with the occurrence of back pain.…”
Section: Discussionmentioning
confidence: 99%
“…In a study with long-term follow-up, Kurunlahti et al [6] pointed out that there was an association between disc diseases and fatal ischemic heart disease. Furthermore, it has been suggested that patients with ischemic coronary disease have a low MEL production rate, with greater decreases in those with higher risk of cardiac infarction and/or death [22]. Now, it is generally accepted that the existence of advanced aortic atherosclerosis, presenting as calcific deposits in the posterior wall of the aorta, increases a person's risk for development of disc degeneration and is associated with the occurrence of back pain.…”
Section: Discussionmentioning
confidence: 99%
“…Nocturnal secretion of melatonin was lower in patients with coronary artery disease [47,48,49,50]. Nighttime melatonin supplementation reduced nocturnal blood pressure in otherwise untreated hypertensive men [51], nondipping women [52], patients with nocturnal hypertension [53] and in adolescents with type 1 diabetes mellitus [54].…”
Section: Clinical Studies Using Melatonin In Msmentioning
confidence: 99%
“…It has also been pointed out that patients with ischemic heart disease, regardless of their age, have deficits of this hormone. [2][3][4] In the observation of patients with arterial hypertension, it was shown that the group with impaired circadian rhythms of arterial blood pressure (BP), nondippers, had reduced melatonin synthesis. 5,6 A proper circadian BP rhythm is connected with a lower risk of left ventricular hypertrophy or of episodes of myocardial ischemia, both silent and symptomatic, in comparison with nondippers.…”
Section: Introductionmentioning
confidence: 99%